Women’s Knowledge of Sexually Transmitted Diseases in Telafer City, Iraq - Mohmmed Qassim Baktash; Abdul-Aziz Ahmed Aziz (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Knowledge of sexually transmitted diseases (STDs) is essential in protecting women from the devastating effects of these infections. This is the first study that attempts to assess the knowledge about one of the most embarrassing diseases in women with Islamic Turkmen culture.Purpose: This study aimed to assess women’s knowledge of STDs in Telafer City and its association with sociodemographic factors.Methods: This cross-sectional study involved 451 women over 18 years old from Telfer City in Iraq. The study was conducted using a convenient sampling technique from 1 December 2021 to 15 June 2022. The study’s data were collected using a STDs knowledge questionnaire. Descriptive statistics of mean, standard deviation, frequency, and percentage were used to describe sociodemographic characteristics and the level of knowledge of STDs among women. In addition, the inferential statistics of ANOVA and Fisher’s exact test were used to determine the association between the women’s characteristics and knowledge. Results: The study signaled that the overall mean score of knowledge of STDs was (6.67±5.85). The vast majority of participants had a low level of knowledge about STDs (73.8%; n=333). Only about (14.4%; n=64) had moderate knowledge, and approximately (11.8%; n=53) of women were highly knowledgeable about STDs. The study also proved the presence of a statistically significant positive association between women’s knowledge regarding STDs with marital status (p˂0.000) and educational level (p˂0.000).Conclusion: The majority of respondents showed low level of knowledge about STDs. Marital status and educational level were associated with this knowledge. This study necessitates the construction and employment of a women-tailored health education program about STDs in Iraq and Telafer City.